ANALYSIS AND MAPPING OF NATURAL RADIATION DOSE RATES IN MAMUJU REGENCY AND CENTRAL-EASTERN WEST JAVA - Zulfahmi
Measurements of the dose rate of natural radiation have been carried out in two areas, namely the central-eastern part of West Java and the Mamuju Regency, South Sulawesi. The measurement locations are generally carried out on connecting roads between villages and cities and are added to several locations to obtain a map of the dose rate distribution. The radiation dose rate measurement was carried out using a Ludlum Model 19 Series 8 dose rate measuring instrument which can measure gamma radiation (?). The position of the measurement location points was recorded as the coordinates of the measurement point using the Garmin Etrex 10 GPX. The total measurement points in the two areas were 283 points with 103 points in West Java and 180 points in Mamuju. The measurement results show that there are significant differences between the two measured areas, for the West Java region covering nine districts, it was found that the average dose rate measured was 0.0265 ± 0.0050 ?Sv/hour. Meanwhile, for the Mamuju Regency area which includes two sub-districts and six villages, the average radiation dose rate is 0.2853± 0.0125 ?Sv/hour. The average dose rate in the middle-eastern part of West Java is still below the world average radiation dose rate of 2.4 mSv/year with a dose rate of 0.2323±0.0044 mSv/year in the middle-eastern part of West Java while Kab. Mamuju is higher than the world average dose rate, Kab. Mamuju 2,500 ± 0.1095 mSv/year. The data from these two areas was processed using the Surfer 13 application to obtain a dose rate contour map in each region.